The spider genus Medionops Sánchez-Ruiz & Brescovit (Araneae: Caponiidae) in Colombia, with the description of four new species - Martínez, Leonel; Sánchez-Ruiz, Alexander; Bonaldo, Alexandre B. (European Journal of Taxonomy, 2021)
Four new Colombian species of the spider genus Medionops Sánchez-Ruiz & Brescovit, 2017 are described and illustrated: M. carolinae sp. nov. (male and female) from Boyacá department, M. cauca sp. nov. (male) from Cauca department, M. luiscarlosi sp. nov. (male and female) from Caldas department and M. santarosa sp. nov. (male) from Risaralda department. Additionally, the distribution of the type species of M. blades Sánchez-Ruiz & Brescovit, 2017, previously known only from Bogotá, Cundinamarca department, is extended to several localities in the Boyacá department. An updated identification key for all Medionops species is provided.